Does stress induce bowel dysfunction?. (August 2014) - Chang, Yu-Ming; El-Zaatari, Mohamad; Kao, John Y
Abstract : Psychological stress is known to induce somatic symptoms. Classically, many gut physiological responses to stress are mediated by the hypothalamus-pituitary-adrenal axis. There is, however, a growing body of evidence of stress-induced corticotrophin-releasing factor (CRF) release causing bowel dysfunction through multiple pathways, either through the HPA axis, the autonomic nervous systems, or directly on the bowel itself. In addition, recent findings of CRF influencing the composition of gut microbiota lend support for the use of probiotics, antibiotics, and other microbiota-altering agents as potential therapeutic measures in stress-induced bowel dysfunction.